Economic aid and international cost sharing - Pincus, John A. (Baltimore, Maryland : The Rand Corporation ; The Johns Hopkins Press, 1965)
This book examines relations between foreign trade and economic growth and on the magnitude of the future import and capital needs of the less developed nations. It also examines burden-sharing of foreign aid in terms of donor's cost, not recipients' gains. Furthermore, the book examines issues like: efficiency, economy, and equity of foreign aid; a historical review of cost-sharing experiences (from the Universal Postal Union to NATO); an excellent attempt to provide an accurate definition of aid; and a description of the resource transfer to poor countries implicit in international commodity agreements.
"Research ... sponsored by the Department of Defense, under Contract SD-300, monitored by the Assistant Secretary of Defense (International Security Affairs)"
Includes index.
Includes bibliographical references: p. 194-201.
lje 14/05/2018
Loans
Keywords: Economic assistance; International economic relations; Economic development; Developing countries